Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3386/w24203
|View full text |Cite
|
Sign up to set email alerts
|

Do School Spending Cuts Matter? Evidence from The Great Recession

Abstract: The statements made and views expressed are solely the responsibility of the authors. Wigger and Xiong are grateful for financial support from the US Department of Education, Institute of Education Sciences through its Multidisciplinary Program in Education Sciences (Grant Award # R305B140042). The views expressed herein are those of the author and do not necessarily reflect the views of the National Bureau of Economic Research. At least one co-author has disclosed a financial relationship of potential relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 11 publications
7
46
0
Order By: Relevance
“…Our findings also provide additional evidence to Jackson et al (2018), who examine whether the academic consequences of spending losses are similar to equivalently sized spending gains. Using data from the NAEP, Jackson et al (2018) find that a $1,000 per pupil decline in school spending reduces student achievement by, on average, 0.08 standard deviations. 16 In comparison, Lafortune et al (2018) show that increases in annual per pupil spending of $1,000 following education finance reforms increase student achievement by 0.12 to 0.24 standard deviations.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…Our findings also provide additional evidence to Jackson et al (2018), who examine whether the academic consequences of spending losses are similar to equivalently sized spending gains. Using data from the NAEP, Jackson et al (2018) find that a $1,000 per pupil decline in school spending reduces student achievement by, on average, 0.08 standard deviations. 16 In comparison, Lafortune et al (2018) show that increases in annual per pupil spending of $1,000 following education finance reforms increase student achievement by 0.12 to 0.24 standard deviations.…”
Section: Resultssupporting
confidence: 57%
“…16 In comparison, Lafortune et al (2018) show that increases in annual per pupil spending of $1,000 following education finance reforms increase student achievement by 0.12 to 0.24 standard deviations. Jackson et al (2018) suggest that the difference in effect sizes for equivalent spending changes indicate that negative shocks to school spending are not as impactful as positive shocks. Results from our analysis suggest that negative shocks to school spending may be more similar in magnitude (in absolute terms) as positive shocks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hira and Gopalaswamy (2019) emphasize the need for reforming skilled immigration policies. However, both studies fail to identify the likely reasons for dependence on international students and talents: (i) cuts in US education budgets (Bound et al, 2016) which has forced universities to depend on international students and even multinationals for education finance and (ii) cuts in advanced placement classes at the pre-university levels, which short-changes many US students (Jackson et al, 2018;Hyman, 2017;Card and Payne, 2002). 15 Furthermore, although Bound et al (2017) found that H-1B visas lead to decline in wages in the US, a result disputed by other studies (Peri et al, 2015;Kerr et al, 2015), it was also found that the lack of preparation of the US students 16 , which results in poor quality, does matter (Richey and Rosburg, 2017;Bound et al 2010).…”
Section: (Iii) Consequences Of International Studentsmentioning
confidence: 99%
“…On the other hand, advocates have argued that competition created by charter schools can be -a tide that lifts all boats‖ by pushing public schools to increase efficiency (Hoxby, 2003b). Given the financial constraints many school districts faced after the Great Recession (Hull, 2010;Jackson, Wigger, & Xiong, 2018) and the growing number of charter schools (NCES, 2018), the question of how charter schools influence districts' student composition, costs, and efficiency is more salient than ever.…”
Section: Introductionmentioning
confidence: 99%